Breast feeding pattern and its relationship with mothers\' weight - Parvin Shahri; Tayebe Balooty; Nasrin Saadati; Mohammad Hossin Haghighi Zadeh (Payesh, 2012)
Objective (s): To examine the relationship between maternal weight and breastfeeding initiation and duration.Methods: This research is an analytical and cross-sectional study which has been done during 2007-2008. Data were collected through questionnaire and interview. Sample consisted of mothers of children 6-12 month attending to west Ahvaz health centers and 150 mothers were selected randomly.Results: mean prepregnancy weight and mean maternal prepregnancy BMI were 65.46±13.1kg, and 25.62 ±5.1 kg respectively. Most common (%72.7) method of infant nutrition was exclusively breast feeding. There was no association between maternal BMI and feeding patterns. BMI showed a significant relationship with duration of each BF and number of feedings per 24 hours. (P<0.01) although after using multivariate regression just daily number of breastfeeding was related to duration of breast feeding. (P<0.05) There was found a significant relationship between delivery mode and postpartum initiation of breast feeding (P<0.01). Conclusion: Mother's weight has adverse effect on daily number of breast feedingIn this study Mother's weight has no effect on pattern of breast feeding, so it seems to clear these issue further studies should carry out.